2017
DOI: 10.1016/j.matlet.2016.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porous yttria-stabilized zirconia microspheres by ultrasonic spray pyrolysis

Abstract: A B S T R A C THigh yield synthesis of yttria-stabilized zirconia (YSZ) porous microspheres can enable application in advanced thermal barrier coatings, exploiting reflective properties originated from high temperature photonics. The complexity of typical wet-chemistry processes utilized in microspheres manufacturing limits yield and can hardly deliver stable porous structures. Here, ultrasonic spray pyrolysis was utilized to produce high quantities of porous YSZ. Droplets of an aqueous precursor solution were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the other hand, the powders must be granule grains, so the temperature should be sufficient to improve the agglomeration. Perez-Page et al investigated yttria stabilized zirconia powders with the USP system for temperatures between 700 °C and 1200 °C and revealed that these powders were crystallized at 700 °C temperature and the crystallization increased depending on the increase in reactor temperature [29]. In our present study, the selected reactor temperature was relatively low.…”
Section: Properties Of Usp Granule Particlesmentioning
confidence: 51%
“…On the other hand, the powders must be granule grains, so the temperature should be sufficient to improve the agglomeration. Perez-Page et al investigated yttria stabilized zirconia powders with the USP system for temperatures between 700 °C and 1200 °C and revealed that these powders were crystallized at 700 °C temperature and the crystallization increased depending on the increase in reactor temperature [29]. In our present study, the selected reactor temperature was relatively low.…”
Section: Properties Of Usp Granule Particlesmentioning
confidence: 51%
“…USP was carried out by following the method described by Perez‐Page et al [ 65 ] and is shown in the lower portion of Figure . Zirconium (IV) oxynitrate hydrate (99%, Sigma‐Aldrich, Saint Louis MO) and yttrium (III) nitrate hexahydrate (99.9%, Alfa Aesar) were dissolved in deionized water at a cation concentration of 0.4 m (Zr + and Y + combined molarity).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous methods such as pyrolysis [13], plasma spraying [14], plasma electrolytic oxidation [15], chemical/physical vapour deposition [16], pulsed laser deposition [17], electrophoretic deposition (EPD) [18], thermal spraying method [19] have been utilised for the preparation of HA coatings on metallic implants. Among them, the thermal spraying method has gathered widespread attention for in-vivo hard tissue regeneration due to the growth of thin HA coatings on a variety of orthopaedic prosthesis and dental implants [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%